Revitalization of Traditional Knowledge in Natural Resource Management: An Ethnobotanical Study in the Dayak Kenyah Indigenous Community - Ibrahim, Riza; Surya, Dhika (Research Collaboration Community (Rescollacom), 2025)
This study aims to document the ethnobotanical knowledge of the Dayak Kenyah community in East Kalimantan as an effort to preserve culture and the environment. Using a qualitative-descriptive approach with data collection techniques through semi-structured interviews, walking transects, and visual documentation, this study identified 47 plant species utilized by the Dayak Kenyah community. The results showed that the plants were categorized based on their main functions, namely as medicine (38%), food (30%), building materials (19%), and ritual purposes (13%). Several types of key plants such as Tengkawang (Shorea spp.), Sungkai (Peronema canescens), Ulin (Eusideroxylon zwageri), and Katimpun (Uncaria gambir) have important values in the cultural and ecological structure of the community. Custom-based conservation practices such as Tana' Ulen are concrete evidence of the implementation of Traditional Ecological Knowledge (TEK) that supports the sustainability of forest ecosystems. However, there are indications of a decline in the interest of the younger generation in this local knowledge, with only 27.8% of young informants being able to identify more than 10 types of local plants. This study recommends the integration of TEK with modern conservation strategies and the revitalization of traditional knowledge through local culture-based education to ensure the sustainability of valuable traditional ecological knowledge.